Infectious bursal disease: Influence of vvIBDV on immunity to Ranikhet disease at the field level - CHRISTOPHER, D SURESH; MURUGAN, M; SHEELA, S ESNTHER; VENI, M; RAJASHREE, B; RAJENDRAN, M P (The Indian Journal of Animal Sciences, 2013)
The seroepidemiological data of Ranikhet disease (RD) and infectious bursal disease (IBD), before(during 1991-92)and after (during 1993-94) the outbreak of very virulent form of IBD (vvIBD) in Tamil Nadu, were statistically analysed. During 1993-94 the half-life (ty) ofRD-matemally derived antibodies (RD-MDA) was 3.2 days and the IBD-MDA was 4.11 days in clean premises. In the infected premises t1/2 of the RD-MDA was 2.69 days and the t1/2 of RD-vaccinal antibodies was 1.85 days. The observed RD vaccinal titres of samples collected during 1993-94 are significantly lower than the statistically predicted lll-titres (using 1991-92 titres as the base), for that age. Mathematical conclusions indicate that vvIBDV could be the cause of this perceived difference in the RD-HI titre values.